Cardiac Tamponade Revisited: A Postmortem Look at a Cautionary Case - Ariyarajah, Vignendra (2007)
Cardiac tamponade is a life-threatening clinical syndrome that requires timely diagnosis. Herein, we present an instructive case of a patient who had cardiac tamponade. The condition went undiagnosed and resulted in the patient's death because almost all of the pathognomonic clinical findings of tamponade were unrecognized or not manifest. To better prepare health care professionals for similar challenges, we discuss the symptoms and clinical signs typical of cardiac tamponade, review the medical literature, and highlight current investigative methods that enable quick, efficient diagnosis and treatment.